The best American mystery stories 2017 - Allyn, Douglas; Allyn, Jim, 1944-; Bevacqua, Dan; Box, C. J.; Brightwell, Gerri; Coney, S. I.; Corey, Trina; Deaver, Jeffery; DuBois, Brendan; Estleman, Loren D.; Harper, Charles John; Johnson, Craig, 1961-; et al. (Best American series., 2017)
From an isolated Wyoming ranch to the Detroit boxing underworld, and from kidnapping and adultery in the Hollywood Hills to a serial killer loose in a nursing home, The Best American Mystery Stories 2017 hosts an abundance of crime, psychological suspense, and bad intentions.